2020
DOI: 10.3390/s20236709
|View full text |Cite
|
Sign up to set email alerts
|

Review of MAC Protocols for Vehicular Ad Hoc Networks

Abstract: Vehicular ad hoc networks (VANETs) need to support the timely end-to-end transmissions of safety and non-safety messages. Medium access control (MAC) protocols can ensure fair and efficient sharing of channel resources among multiple vehicles for VANETs, which can provide timely packet transmissions and significantly improve road safety. In this paper, we review the standards of some countries for VANETs. Then, we divide the MAC protocols proposed for VANETs into single-channel MAC protocols and multi-channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…It works in two frequency bands, 5 GHz using the OFDM mechanism. In the second case, communication works in the range of 5.9 GHz divided into smaller operation channels named from A to D. Version A works with the frequency of 30 MHz for safety messages, version B with the frequency of 20 MHz for non-safety messages and version C works revision, which merged the channels 174 and 176 into the channel 175 and the channels 180 and 182 into the channel 181 [26]. The mentioned spectrum can be seen in Figure 4.…”
Section: Physical and Mac Layermentioning
confidence: 99%
“…It works in two frequency bands, 5 GHz using the OFDM mechanism. In the second case, communication works in the range of 5.9 GHz divided into smaller operation channels named from A to D. Version A works with the frequency of 30 MHz for safety messages, version B with the frequency of 20 MHz for non-safety messages and version C works revision, which merged the channels 174 and 176 into the channel 175 and the channels 180 and 182 into the channel 181 [26]. The mentioned spectrum can be seen in Figure 4.…”
Section: Physical and Mac Layermentioning
confidence: 99%
“…The authors have noted that the mobility features of VANETs is not well considered and the merging collision issue is not well addressed which resulted in a high delay and packet loss. Ma et al 18 have presented a thorough review of MAC protocols designed for VANETs by classifying them into single and multichannel MAC protocols, which are further divided into distributed and centralized MAC protocols while comparing their typical protocols. They have founded that no current MAC protocol can solve simultaneously the problems of fairness, low latency, and high reliability while considering the high dynamic network topology changes.…”
Section: Related Workmentioning
confidence: 99%
“…They have concluded that their scheduling techniques proposed to overcome the challenges mentioned above didn't provide an effective solution to the problem of high mobility that delays and degrades the deliverance of warning messages. MAC schemes proposed for vehicular networks have been reviewed and compared in Ma et al, 26 and it was concluded that they cannot provide fairness, predictable delays, and good reliability all together while regarding the frequent topology changes.…”
Section: Related Workmentioning
confidence: 99%